Analysis of Teachers' Efforts to Apply Gamification Methods in Learning Christian Religious Education for Grade V - Angelika Amanda Octaviana; Prasetiawati Prasetiawati; Dwi Sartica (EDUJAVARE: International Journal of Educational Research, 2026)
Education plays a crucial role in developing students’ knowledge, character, behavior, and skills in accordance with the demands of the modern era. This study aims to describe the implementation of gamification in Christian Religious Education learning and the teacher’s efforts to evaluate student learning outcomes in fifth-grade students at SD Negeri 1 Panarung. The research employed a qualitative descriptive method with data collected through observation, interviews, and documentation involving one Christian Religious Education teacher and fifth-grade students. The findings reveal that gamification was implemented through careful lesson planning and the integration of game elements such as points, rewards, quizzes, educational games, and Superbook videos to create a more interactive, enjoyable, and meaningful learning environment. The teacher used gamification not only to increase students’ motivation, participation, and understanding of the material, but also to maintain the spiritual and moral objectives of Christian Religious Education. In evaluating learning outcomes, the teacher applied continuous and process-oriented assessment through quizzes, oral questioning, classroom observation, group activities, and direct feedback in the form of points and rewards. The evaluation covered students’ cognitive understanding, memory of the lesson, classroom engagement, confidence, cooperation, and enthusiasm during the learning process.